Development of Ni–Ce/Al-MCM-41 catalysts prepared from natural kaolin for CO2 methanation - Walairat Uttamaprakrom (2022)
We prepared Ni–Ce/Al-MCM-41 catalyst with enhanced activity at low temperatures via one-pot hydrothermal synthesis using kaolin as a silica precursor for CO2 methanation and investigated the influence of Ce addition on the catalytic activity enhancement. The as-synthesized Al-MCM-41 possessed hexagonal mesoporous silica with a surface area of 436 m2/g and a mesopore of 3.8 nm, allowing the incorporation of Ni and Ce into the Al-MCM-41 structure. In a fixed-bed tubular reactor, the catalytic performance of the as-prepared catalyst was evaluated in terms of CO2 conversion, CH4/CO selectivity, CH4 yield, reaction rates per catalyst mass (rm), and catalyst surface (rs), TOF, activation energy, and the deactivation rates of its corresponding activities at 250–550 °C and 1 atm. As the Ce content increased, the catalytic activity greatly improved due to the improved Ni dispersion and higher CO2 adsorption, although the porosity of the catalyst significantly decreased. With the optimum Ce content, 100% CH4 yield was achieved at 350 °C and weight hourly space velocity (WHSV) = 20,000 mL g−1 h−1. The optimum catalyst also exhibited high stability with a deactivation rate of −0.072% YCH4 g−1 h−1 over 76 h, attributed to the strong interaction between Ce and Al in Al-MCM-41.